Protein kinase C-dependent activation of P44/42 mitogen-activated protein kinase and heat shock protein 70 in signal transduction during hepatocyte ischemic preconditioning - Gao, Yi (World J Gastroenterol, 2004)
AIM: To investigate the significance of protein kinase C (PKC), P44/42 mitogen-activated protein kinase (MAPKs) and heat shock protein (HSP)70 signal transduction during hepatocyte ischemic preconditioning. METHODS: In this study we used an in vitro ischemic preconditioning (IP) model for hepatocytes and an in vivo model for rat liver to investigate the significance of protein kinase C (PKC), P44/42 mitogen-activated protein kinase (P44/42 MAPKs) and heat shock protein 70 (HSP70) signal transduction in IP. Through a normal liver cell hypoxic preconditioning (HP) model in which cultured normal liver cells were subjected to 3 cycles of 5 min of incubation under hypoxic conditions followed by 5 min of reoxygenation and subsequently exposed to hypoxia and reoxygenation for 6 h and 9 h respectively. PKC inhibitor, activator and MEK inhibitor were utilized to analyze the phosphorylation of PKC, the expression of P44/42 MAPKs and HSP70. Viability and cellular ultrastructure were also observed. By using rat liver as an in vivo model of liver preconditioning (3 cycles of 10-min occlusion and 10-min reperfusion), in vivo phosphorylation of PKC and P44/42MAPKs, HSP70 expression were further analyzed. AST/ALT concentration, cellular structure and ultrastruture were also observed. All the data were statistically analyzed. RESULTS: Similar results were obtained in both in vivo and in vitro IP models. Compared with the control without IP (or HP), the phosphorylation of PKC and P44/42 MAPKs and the expression of HSP70 were obviously increased in IP (or HP) treated model in which cytoprotection could be found. The effects of preconditioning were mimicked by stimulating PKC with 4β phorobol-12-myristate13-acetate (PMA). Conversely, inhibiting PKC with chelerythrine abolished the protection given by preconditioning. PD98059, inhibitor of MEK (the upstream kinase of P44/42MAPKs), also reverted the cytoprotection exerted by preconditioning. CONCLUSION: The results demonstrate that preconditioning induces a rapid activation of P44/42MAPKs and PKC activation plays a pivotal role in the activation of P44/42 MAPKs pathway that participates in the preservation of liver cells. HSP expression is regulated by signals in PKC dependent P44/ 42 MAPKs pathway.